Microglia Loss and Astrocyte Activation Cause Dynamic Changes in Hippocampal [18F]DPA-714 Uptake in Mouse Models of Depression - Guo, Jiamei; Qiu, Tian; Wang, Lixia; Shi, Lei; Ai, Ming; Xia, Zhu; Peng, Zhiping; Zheng, Anhai; Li, Xiao; Kuang, Li (Frontiers in Cellular Neuroscience, 2022)
Major depression is a serious and chronic mental illness, but the etiology are poorly understood at present. Glial cells have been increasingly implicated in the pathogenesis of depression. Unfortunately, the specific role of microglia and astrocytes in stress-induced depression remains unclear. TSPO has long been considered to be a marker of neuroinflammation or microglial activation, but in fact it is also located on astrocytes. Thus, it’s unscientific to equated elevated TSPO with a marker of microglial activation. Moreover, the dynamic interactions among TSPO, microglia, and astrocytes in the context of depression have not been explored. In the present study, C57BL/6J male mice were subjected to chronic unpredictable stress (CUS) for 5 weeks. Subsequently, sucrose preference and tail suspension tests were performed in order to assess anhedonia and despair in this mice. [18F]DPA-714 positron emission tomography was adopted to dynamically assess the changes in glial cells before and after 2, 4, or 5 weeks of exposure to CUS. The number of TSPO+ cells, Iba-1+ microglial cells, TSPO+/Iba-1+ cells, GFAP+ astrocytes, and TSPO+/GFAP+ cells in the hippocampus and each hippocampal subregion was quantified using immunofluorescence staining. Real-time PCR was used to evaluate TSPO expression in the hippocampus. We observed that hippocampal [18F]DPA-714 uptake significantly increased after 2 weeks of CUS, but the signal significantly decreased after 5 weeks of CUS. CUS significantly reduced the density of Iba-1+, TSPO+, and TSPO+/Iba-1+ cells in the hippocampus, especially in the CA1 and DG regions. However, this intervention increased the density of GFAP+ astrocytes in the CA2/CA3 regions of the hippocampus. These results showed that the dynamic changes in hippocampal [18F]DPA-714 uptake after CUS at least were caused by a combination of dynamic changes in microglia and astrocytes in different hippocampal subregions. Therefore, the dynamic assessment of different glial states at different stages and in different brain regions might help to explore the etiology of depression and develop new treatment methods for the illness.